Implementation Of The Molina System On The Performance Of Foreign Resident Consulting Services - Pertiwi, Dea Tata; Abdi, Muhammad Nur (Journal of Collaborative Industrial Management (JCIM), 2025)
Digital transformation in public administration has become essential for improving service efficiency and transparency. This study examines the implementation of the Foreigners Traffic Module (MOLINA) system by Indonesia's Directorate General of Immigration and its impact on organizational performance, particularly in foreign resident consulting services. Using a descriptive qualitative research approach, data were collected through in-depth interviews, observations, and documentation from five informants with direct experience using MOLINA since its launch in 2023. The findings reveal that MOLINA implementation significantly enhances operational workflow efficiency, data verification speed, and service transparency. However, the system faces technical constraints, including server stability issues, inadequate data synchronization, and limited document size capacity, that require organizational adaptation. The study contributes to understanding how digital systems influence organizational performance and service quality in collaborative public-private settings. This research offers practical insights for both immigration authorities and consulting service providers in managing digital transformation initiatives, emphasizing the importance of technical improvements and user training programs.